Managing stage fright a guide for musicians and music teachers - Nagel, Julie Jaffee (Oxford University Press, 2017)
"Why is it that well-prepared, talented, hardworking, and intelligent performers find their performance and self-esteem undermined by the fear of memory slips, technique failures, and public humiliation? In Managing Stage Fright: A Guide for Musicians and Music Teachers, author Julie Jaffee Nagel unravels these mysteries, taking the reader on an intensive backstage tour of the anxious performer's emotions to explain why stage fright happens and what performers can do to increase their comfort in the glare of the spotlight. Examining the topic from her interdisciplinary educational, theoretical, clinical, and personal perspectives, Nagel uses the music teacher/student relationship as a model for understanding the performance anxiety that affects musicians and non-musicians alike. Shedding new light on how the performer's emotional life is connected to every other facet of their life, Managing Stage Fright encourages a deeper understanding of anxiety when performing. The guide offers strategies for achieving performance confidence, emphasizing the relevance of mental health in teaching and performing. Through the practices of self-awareness outlined in the book, Nagel demonstrates that it is possible and desirable for teachers to assist students in developing the coping skills and attitudes that will allow them to not feel overwhelmed and powerless when they experience strong anxiety. Each chapter contains insights that help teachers recognize the symptoms-obvious, subtle, and puzzling-of the emotional grip of stage fright, while offering practical guidelines that empower teachers to empower their students. The psychological concepts offered, when added to pedagogical techniques, are invaluable in music performance and in a variety of life situations since, after all, music lessons are life lessons."--Provided by publisher.